2022
DOI: 10.1126/scitranslmed.abn1926
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and epigenomic BRCA alterations predict adaptive resistance and response to platinum-based therapy in patients with triple-negative breast and ovarian carcinomas

Abstract: Triple-negative breast cancer (TNBC) and ovarian carcinomas (OvCas) with BRCA1 promoter methylation ( BRCA1 meth) respond more poorly to alkylating agents compared to those bearing mutations in BRCA1 and BRCA2 ( BRCA mut). This is a conundrum given the biologically equivalent homologous recombination deficiency (HRD) induced by these genetic and epigenetic BRCA perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Different platinum-resistant BRCA1 methylated models show significant BRCA1 gene expression, associated with a low percentage of BRCA1 methylation and increased levels of RAD51 foci upon cisplatin treatment, supporting incomplete promoter methylation as potential mechanism of platinum resistance in these tumours. This is in accordance with recent studies demonstrating that biallelic BRCA1/2 inactivation was required for response to PARP inhibitors and platinum 31 33 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Different platinum-resistant BRCA1 methylated models show significant BRCA1 gene expression, associated with a low percentage of BRCA1 methylation and increased levels of RAD51 foci upon cisplatin treatment, supporting incomplete promoter methylation as potential mechanism of platinum resistance in these tumours. This is in accordance with recent studies demonstrating that biallelic BRCA1/2 inactivation was required for response to PARP inhibitors and platinum 31 33 .…”
Section: Discussionsupporting
confidence: 93%
“…A positive correlation between the presence of BRCA1/2 mutations and platinum-based therapy was found in several studies both in the neo-adjuvant and metastatic setting 7 , 25 – 27 , although not in others 28 , 29 . We find no correlation between cisplatin response and BRCA1 methylation, in line with recent studies 25 , 30 , 31 . Different platinum-resistant BRCA1 methylated models show significant BRCA1 gene expression, associated with a low percentage of BRCA1 methylation and increased levels of RAD51 foci upon cisplatin treatment, supporting incomplete promoter methylation as potential mechanism of platinum resistance in these tumours.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the 3D-HRD assay did not include BRCA1 promoter DNA methylation, which was considered in the Myriad HRD assay. A recent study has found that BRCA1 promoter DNA methylation is a functionally plastic state that is depleted rapidly after exposure to chemotherapy, and BRCA1 methylation status was not associated with a survival advantage 52 .…”
Section: Discussionmentioning
confidence: 99%
“…BReast CAncer genes ( BRCA ) 1 and 2 encode DNA repair enzymes and took their name just because of their association with BC [ 33 , 34 ]. BRCA mutations are highly associated with TNBC, as well as the loss of BRCA1 or BRCA2 activity [ 35 ]. Phosphatase and Tensin homolog deleted on chromosome 10 ( PTEN ) is a tumor suppressor gene located in the 10q23 region of chromosome 10 that has been found to be mutated in many types of cancers, including BC, and encodes for a dual lipid and protein phosphatase [ 36 ].…”
Section: Genetic Mutations In Bcsmentioning
confidence: 99%